Natural product derivative activates autophagy in cancer cells - Andong Koung Edzidzi, Ursula-Claire (Division of Medical Biochemistry and Structural Biology, 2017)
Artemisinin, a natural product and its derivatives are potent antimalarial compounds, which have shown anticancer activity. In this study, we further characterized a novel artemisinin derivative namely EXP57EA which was previously designed and synthesized by the Chemistry Department at the University Of Cape Town. We determined the effect of EXP57EA on a panel of cancer cell lines, characterized the mode of cell death and also performed preliminary investigations of the signaling pathways that trigger the mode of cell death. Dihydroartemisinin (DHA), EXP57EA and cisplatin were screened on a selected panel of cancer cell lines: 3 esophageal cancer cell lines WHCO1, WHCO5, KYSE150; one breast cancer cell line MDA-MB-231 and one cervical cancer cell line SiHa. The 3-[4, 5-dimethylthiazol-2-yl]-2, 5- diphenyltetrazolium bromide (MTT) assay, and analysis with GraphPad prism software were used to calculate IC₅₀ values. EXP57EA displayed toxicity in the panel of cancer cell lines studied, and had lower IC₅₀ values (IC₅₀ values were ranging from 15.8 μM to 25.1 μM) than DHA and cisplatin. DHA was only active in two cells lines: WHCO1 (21.3 μM) and WHCO5 (77.3 μM), IC₅₀ values of cisplatin were ranging from 31.2 μM to 108.1 μM. EXP57EA was further investigated to understand the mode of cell death activated in the panel of cancer cell lines. The results showed that EXP57EA did not induce apoptosis in any of the cell lines studied, whereas DHA induced apoptosis, based on the PARP cleavage assay. In contrast, treatment with EXP57EA induced the appearance of vacuoles in treated cells compared to untreated cells, which was suggestive of autophagy. Autophagy was monitored by analyzing the expression level of two autophagy markers, Beclin1 and LC3-II by western blot. It was observed that EXP57EA treatment caused changes in the expression levels of both Beclin1 and LC3-II. We showed that EXP57EA induced elevated levels of autophagy, based on an increase in the flux of autophagy in the treated cells, since the lysosomal inhibitors ammonium chloride (NH₄Cl) and chloroquine substantially blocked LC3-II turnover in WHCO1 (confirmed previous result in our laboratory) and SiHa cancer cell lines. Furthermore, we also showed that treatment with EXP57EA resulted in increased expression of CHOP (by Real-Time PCR), and activated the PERK/eIF2α pathway, since treatment of WHCO1 cells with EXP57EA stimulated phosphorylation of eIF2α, suggesting that ER stress might be involved in mediating EXP57EA-induced cell death. Our results also suggested that EXP57EA activated the JNK pathway since treatment of WHCO1 and WHCO5 cells with EXP57EA stimulated phosphorylation of cjun and resulted in elevated levels of total c-jun. These results suggested the JNK pathway might also be involved in EXP57EA-induced cell death. However, the proposed involvement of the PERK/eIF2α pathway and the JNK pathway in EXP57EA-mediated autophagy is of a preliminary nature, and further work will have to be done to confirm the involvement of these pathways. This study showed that EXP57EA may have potential as an anticancer drug lead.